2022
DOI: 10.37622/gjpam/18.2.2022.433-452
|View full text |Cite
|
Sign up to set email alerts
|

NILA – An Innovative Technique for Optimality Testing and Optimizing a Solution in Assignment Problems

Abstract: In this research article, we propose a very simple and innovative iterative technique named NILA (equivalent name for the MOON in the classical Tamil language) for optimality testing and also optimization of a solution obtained by a method in assignment problems. The NILA technique has been tested on a number of near optimal and optimal solutions obtained for many balanced and unbalanced assignment problems by several other available methods. Testing results validate that the proposed NILA technique is the ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The readers are requested to refer the article [6] due to Murugesan R. for the detailed algorithm of the MODA method.…”
Section: Algorithm For the Existing 'Moda' Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The readers are requested to refer the article [6] due to Murugesan R. for the detailed algorithm of the MODA method.…”
Section: Algorithm For the Existing 'Moda' Methodsmentioning
confidence: 99%
“…In 2022, Murugesan R. [6] proposed an innovative method named MODA (Modified Allocation) which tests the optimality of a solution and also optimizes the solution, if it is not optimal. By our further research we have identified the extra efforts made in the MODA method to trace and consider all possible loops starting and ending at an identified basic cell and passing through a non-basic cell.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2022, Murugesan R. [4] proposed an innovative method named MODA (Modified Allocation) which tests the optimality of a solution and also optimizes the solution, if it is not optimal. By our further research we have identified the extra efforts made in the MODA method to trace and consider all possible loops starting and ending at an identified basic cell and passing through a non-basic cell.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, we have simplified this difficulty by introducing the new idea of Solution Improvement Loops only to consider. This resulted in a revised version of the existing MODA method [5].…”
Section: Introductionmentioning
confidence: 99%